Pemanfaatan Beton Ringan Sebagai Rumah Lebah Madu Linot Di Desa Ie Seum Kecamatan Mesjid Raya Kabupaten Aceh Besar - Fatimah, Eldina; Abdullah, Abdullah; Halim, Agus; Fauzi, Muhammad; Nasaiy, Qurratul 'Aini Benti (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2024)
Honey as a natural product produced by bees, has high health qualities and economic value. There are diverse species of bees known to produce honey with essential nutrients such as vitamin C. Trigona bees (Apidae), also known as Linot (in Acehnese language), are one type of bee that is easy to raise and harmless. This species makes nests in hollows of trees, bamboo trunks, wooden burrows, and even crevices in fences, walls and walls of houses. Generally, farmers use houses for storing bee honey made from simple materials in the form of wood, bamboo. This material was chosen because it is similar to the original habitat of bees and can provide ideal conditions for colonies. In the selection of honey facilities and houses, things that need to be considered are the ability of the material to maintain a stable temperature in the hive (because temperature is very important for colony life), resistance to predators and extreme weather, and ease in maintaining and harvesting honey. This paper aims to explain the use of lightweight concrete as an alternative to honey houses. Lightweight concrete is lightweight concrete, has good thermal insulation properties and is resistant to fire and heat. The installation of the Linot honey house was applied in Ie Seum Village as a beneficiary village for the service activities carried out. It can be seen that linot bees still use honey houses to store their honey and the honey production produced is not much different from other honey houses.